Knowledge, Attitude and Practice of Prevention of Thalassaemia of the Parents of Children with Thalassaemia attending in a Tertiary Care Hospital in Bangladesh - Begum, Fardoushi; Shirin, Mst Farhana; Sayed, Md Abu; Sharmin, Laila Shamima; Uddin, Md Belal (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Inherited disorder of Hemoglobin is widely distributed throughout the world. Among them, Thalassaemia is a common disorder with widespread geographical distribution. Objectives: The objective of the study was to determine the level of knowledge, attitude and practice of thalassaemia prevention among parents of children with Thalassaemia. Methodology: This was a descriptive cross sectional study. This study was conducted in inpatient and outpatient department of paediatrics, Rajshahi Medical College Hospital over a period of July 2020 to June 2021. 45 parents of children with thalassaemia were purposively selected as study subjects. Informed written consent were obtained from the parents before enrollment in the study. Data were collected on variables of interest. All the findings were recorded and analyzed. Statistical analysis were done using statistical package for social science (SPSS) software version 21. Result: Total 45 parents of children with thalassaemia were enrolled in the study. Among the informants, 73.3% (total 33) were mother and 26.6% (total 12) were father. 77.7% (total 35) children were from rural areas and 22.22% (total 10) were from urban areas. All the study population received knowledge about thalassaemia from the physicians. Knowledge of the parents about the disease, its treatment options and methods of its prevention were assessed by likert scale questionnaire. 22.22% parents had adequate knowledge , 64.44% had average knowledge and 13.33% had inadequate knowledge about the disease. 60% parents had adequate knowledge 31.11% had average knowledge and 8.89% had inadequate knowledge about prevention of thalassaemia. Attitude of all the parents (100%) were positive. Conclusion: Most of the parents have adequate knowledge and positive attitude for thalassaemia prevention and they can serve as resource for spreading awareness about thalassaemia in community. J Bangladesh Coll Phys Surg 2024; 42: 6-11